Single and multiple dose intravenous and oral pharmacokinetics of the hedgehog pathway inhibitor vismodegib in healthy female subjects - Graham, Richard A.; Hop, Cornelis E. C. A.; Borin, Marie T.; Lum, Bert L.; Colburn, Dawn; Chang, Ilsung; Shin, Young G.; Malhi, Vikram; Low, Jennifer A.; Dresser, Mark J. (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • While recent publications have suggested the pharmacokinetics (PK) of vismodegib appear to be non‐linear, there has not been a report describing the mechanisms of non‐linearity. WHAT THIS STUDY ADDS • This study provides evidence that two separate processes, namely, solubility‐limited absorption and concentration–dependent plasma protein binding, can explain the non‐linear PK of vismodegib. This study provides quantitative results which can account for the lower than expected accumulation of vismodegib with continuous daily dosing. AIM Vismodegib has demonstrated clinical activity in patients with advanced basal cell carcinoma. The pharmacokinetics (PK) of vismodegib are non‐linear. The objective of this study was to determine whether vismodegib PK change following repeated dosing by administering a tracer intravenous (i.v.) dose of 14C‐vismodegib with single and multiple oral doses. METHODS Healthy post menopausal female subjects (n= 6/group) received either a single or daily 150 mg vismodegib oral dose with a 14C‐labelled 10 µg i.v. bolus dose administered 2 h after the single or last oral dose (day 7). Plasma samples were assayed for vismodegib by LC‐MS/MS and for 14C‐vismodegib by accelerator mass spectrometry. RESULTS Following a single i.v. dose, mean clearance, volume of distribution and absolute bioavailability were 43.4 ml h−1, 16.4 l and 31.8%, respectively. Parallel concentration–time profiles following single oral and i.v. administration of vismodegib indicated elimination rate limited PK. Following i.v. administration at steady‐state, mean clearance and volume of distribution were 78.5 ml h−1 and 26.8 l, respectively. Comparison of i.v. PK parameters after single and multiple oral dosing showed similar half‐life, increased clearance and volume of distribution (81% and 63% higher, respectively) and decreased bioavailability (77% lower) after repeated dosing. Relative to single dose, the unbound fraction of vismodegib increased 2.4‐fold with continuous daily dosing. CONCLUSION Vismodegib exhibited a long terminal half‐life after oral and i.v. administration, moderate absolute bioavailability and non‐linear PK after repeated dosing. Results from this study suggest that the non‐linear PK of vismodegib result from two separate, non‐linear processes, namely solubility limited absorption and high affinity, saturable plasma protein binding.